Reviewing the National Courts in Creating Orderly International Law and Community - Johanis Leatemia (Faculty of Law, Hasanuddin University, 2017)
Orderly international community and international law are determined by a national court. Essentially, the national court must be competent to maintain the balance between the national interest which based on the national sovereignty as well as the provisions of international law within the framework of peaceful coexistence. This article reviews the role of national courts in creating and developing the customary international law. As it turns out in practice, however, it has certain weaknesses, particularly in view of the accountability and legitimacy aspects of its establishment. This purpose could be achieved if national courts were able to maintain a balance between the national interest based on the sovereignty of State on the one hand and the provisions of international law on the other. The function of the national court was to maintain a balance between international law and national law.